Emerging models of social enterprise in Eastern Asia: a cross-country analysis - Defourny, Jacques; Kim, Shin-Yang (Social enterprise journal, 2011)
Purpose - This paper aims to compare profiles of social enterprises as they are emerging in China, Hong Kong, Taiwan, Japan and South Korea and to highlight common features across countries allowing the identification of (partly) East-Asian-specific model(s) of social enterprise.Design methodology approach - The paper first examines the socio-economic contexts in which new public policies and new NPOs' initiatives were launched to offer innovative solutions to current challenges, especially unemployment. Interactions between Eastern Asia and Western regions (EU, USA) are also analysed as to experiments and conceptions of social enterprise. In order to identify major convergences and divergences across countries in Eastern Asia, we rely on country studies presented in this issue as well as on a broad literature, related more specifically to the development and roles of NPOs and co-operatives in this region.Findings - Five major models of social enterprise with specific dynamics can be identified in Eastern Asia. State influence and driving forces linked to public policies make these models rather different from the typical US social enterprise; as for the role of civil society, it seems weaker than in Western contexts but is growing significantly. Co-operative movements also play a significant role in shaping some social enterprise models. Finally, two conditions identified as critical for the development of social economy organisations - a "condition of necessity" and a "condition of shared destiny" - seem to be valid in Eastern Asia as well, provided they are properly reinterpreted.Research limitations implications - As in other regions, the concept of social enterprise itself only begins to be used in Eastern Asia, and no specific legislation deals explicitly with social enterprise as such, except in South Korea. So the main challenge was to identify all categories of initiatives which can be described as part of the new "social enterprise phenomenon". The understanding of the latter may evolve over time and vary across countries.Originality value - The present analysis, just like the other four papers in this issue, is a result of a joint research project of the EMES European Research Network and East-Asian researchers. Country studies were conducted along common broad guidelines, and they were discussed and revised at various stages, which insured a fairly good level of comparability. Moreover, this seems to be the first systematic comparative analysis on social enterprise involving all industrialised countries in Eastern Asia.